KONTRIBUSI PEMILIHAN PENOLONG PERSALINAN UNTUK MENCEGAH KEMATIAN IBU DI PROVINSI SUMATERA SELATAN - Ekowati Retnaningsih (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
In the year 2004, maternal mortality rate (MMR) of South Sumatra Province was 467 per 100,000 live births. Target of Healthy South Sumatra 2008 are 175 each 100.000 live births. Based on Blum concept, health seeking behavior factor has strong influence the community health status, including mortality rate. The research objective is to get information about contribution of health seeking behavior factors, specialty birth attendant to prevent maternal mortality. This is case control study. Locations of research are 4 districts in South Sumatra Province, e.g Musi Banyu Asin, Muara Enim, Ogan Ilir, and Palembang in 2007. Respondents of case group were husbands of dead mother and respondent of control group were mothers who were a live. Total sample were 78 mothers, from case group were 26 mothers and control group were 52 mothers.Results of the research were 1) Attributable Fraction Effect (AFE) was 0.78 and 2) Attributable Fraction Effect of Population (AFP) was 0.35. Conclusion of the researches was health behavior to choose kind of birth attendant influence maternal mortality. The choice of health provider as birth attendant has contribution 78% to prevent maternal mortality at group of mother who were choose non-health providers as birth attendant and has contribution 35% to prevent maternal mortality in population. A recommendation of further research is to do qualitative research to get information about cause of pregnancy women choose non-health provider as birth attendant.